ON SOME ACTUAL ASPECTS OF INTERPRETATION OF THE THEORY OF MODERNIZATION - Gutorov, V.A. (RUDN Journal of Political Science, 2018)
The purpose of this article is to summarize the diverse aspects of scientific discussion revolving around the notion itself and complicated questions of the modern theory of modernization. One of the main point of discussion is the new relationship between once so dissimilar conceptions like modernization, democratization and globalization. These conceptions have been brought together in the end of the XXth century and since that time usually discussed interconnected, often maintaining a heterogeneous sense. The terms “modernization” and “globalization” have come to be emotionally charged in public discourse. For some, they imply the promise of an international civil society, conducive to a new era of peace and democratization. For others, they imply the threat of an American economic and political hegemony, with its cultural consequence being a homogenized world. Nevertheless, some distinct characteristics defining the general tendencies of the modernization process really exist. The main tendency is the changing meaning of modernity, or the emergence of “alternative modernities”. There is also the increasingly significant phenomenon of alternative globalizations that is, cultural movements with a global outreach originating outside the Western world and indeed impacting on the latter. The second trend is related to a crisis in the legitimacy of the nation-state tradition forcing to review the problem of the role of democracy in the modern world. S.M. Lipset's observation that democracy is related to economic development, first advanced in 1959, has generated the largest body of research on any topic in political science. Yet there are two distinct reasons this relation may hold: either democracies may be more likely to emerge as countries develop economically (S.P. Huntington, R. Inglehart), or they may be established independently of economic development but may be more likely to survive in developed countries. The basic assumption of the theory of modernization, in any of its versions, is that there is one general process of which democratization is but the final stage. Modernization consists of a gradual differentiation and specialization of social structures that culminates in a separation of political structures from other structures and makes democracy possible. But now a prevailing view, according to which the emergence of democracy is not a by-product of economic development (G. O’ Donnell). The protagonists of this approach do not believe that the fate of democratic rule would be determined exclusively by current levels of economic development. They maintained that, albeit within constraints, democratization was an outcome of actions, not just of economic conditions as like as historical past (A. Giddens, R.M. Unger).